Early reading learning for special needs students: challenges on inclusive primary school during COVID-19 pandemic - Asri, Dahlia Novarianing; Cahyono, Bambang Eko Hari; Trisnani, Rischa Pramudia (Linguistics and Culture Review, 2021)
This study is meant to describe the types of disability faced by students in inclusive schools and the challenges faced by teachers as well as students in early reading learning for students with special needs in inclusive primary schools during the COVID-19 pandemic. The research was conducted in 12 inclusive primary schools in Magetan Regency, Indonesia. This research is a descriptive qualitative research in which psychological assessment consisting of intelligence tests CPM, and WISC, documentation, passive observation, and in-depth interviews were used to collect the data. The data were collected from informants, events or activities of student interaction in school, and documents of students’ backgrounds and other related documents. The subjects of this study were 72 special needs students with special needs in 12 inclusive primary schools. The data were then analyzed using an interactive analysis model. The results showed that slow learning is the most common type of disability faced by students with special needs in inclusive elementary schools around Magetan Regency, Indonesia. During the COVID-19 pandemic, early reading learning was conducted through distance learning which encountered many obstacles, such as lack of mobile phone due to the low socioeconomic status of parents.